2009
DOI: 10.1152/jn.00688.2009
|View full text |Cite
|
Sign up to set email alerts
|

Been There, Seen That: A Neural Mechanism for Performing Efficient Visual Search

Abstract: In everyday life, we efficiently find objects in the world by moving our gaze from one location to another. The efficiency of this process is brought about by ignoring items that are dissimilar to the target and remembering which target-like items have already been examined. We trained two animals on a visual foraging task in which they had to find a reward-loaded target among five task-irrelevant distractors and five potential targets. We found that both animals performed the task efficiently, ignoring the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
99
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 58 publications
8
99
1
Order By: Relevance
“…This finding was later confirmed by a virtual lesion study which abolished environmental IOR by applying TMS to the right intraparietal sulcus (van Koningsbruggen, Gabay, Sapir, Henik, & Rafal, 2009). In visual foraging tasks, IOR is manifested as delayed behavioral responses (e.g., Klein & Macinnes, 1999;Shariat Torbaghan, Yazdi, Mirpour, & Bisley, 2012) or reduced neuronal responses (Mirpour, Arcizet, Ong, & Bisley, 2009) to previous fixated objects (or locations). Mirpour and Bisley (2012) examined LIP neurons that had remapping responses in a foraging task and observed weaker remapping responses for previously fixated items.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was later confirmed by a virtual lesion study which abolished environmental IOR by applying TMS to the right intraparietal sulcus (van Koningsbruggen, Gabay, Sapir, Henik, & Rafal, 2009). In visual foraging tasks, IOR is manifested as delayed behavioral responses (e.g., Klein & Macinnes, 1999;Shariat Torbaghan, Yazdi, Mirpour, & Bisley, 2012) or reduced neuronal responses (Mirpour, Arcizet, Ong, & Bisley, 2009) to previous fixated objects (or locations). Mirpour and Bisley (2012) examined LIP neurons that had remapping responses in a foraging task and observed weaker remapping responses for previously fixated items.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we also found changes in the inferior occipital gyrus that could be linked to the PPC. On visual search tasks designed to investigate the priority map function, it has been observed that occipital gyrus neurons do not respond to task demands as the PPC does; the PPC responds more to targets than the occipital gyrus (Ipata et al, 2006;Buschman and Miller, 2007;Thomas and Paré, 2007;Mirpour et al, 2009). The decreased activation in occipital gyrus areas could be explained by repetition suppression mechanisms .…”
Section: Resultsmentioning
confidence: 99%
“…Supporting this hypothesis, researchers have been observing that maps in early visual areas do not respond to task demands like the PPC does. For example, during visual search tasks, enhanced PPC response was observed more for targets than for distractors (Ipata et al, 2006;Buschman and Miller, 2007;Thomas and Paré, 2007;Mirpour, Arcizet, Ong and Bisley, 2009). It seems that during visual search tasks, the focus of attention is guided through the visual scene using the priority map, where the targets are highlighted and the distractors are suppressed .…”
Section: Priority Maps and Posterior Parietal Cortexmentioning
confidence: 99%
See 2 more Smart Citations